THE MISERY OF WAR AS SEEN IN STEPHEN CRANE'S WAR IS KINF AND WALT WHITMAN'S DIRGE FOR TWO VETERANS - Luqman Nur Chandra (Lexicon, 2013)
This article discusses two poems, a Stephen Crane’s poem entitled War is Kind and a Walt Whitman’s poem entitled Dirge for Two Veterans. These two poems are about the war.The objectives of the study are to illustrate the misery that is caused by the war and to compare the different way’s of expressing the same theme in these two poems. The approach used in this research is the objective approach. This approach is chosen because the analysis is solely based on the elements found in the poems. This paper uses the library research as the method of research. Then the descriptive method is applied to explain the poems descriptively by interpreting each stanza in the poems.The result of the research shows that the misery which is caused by war exists and affects so many people. Both Stephen Crane’s War is Kind and Walt Whitman’s Dirge for Two Veterans provide us with images of death and misery that are caused by the war though in a slight different way in expressing the theme. War is Kind highlights the irony of ‘war is kind’ to provoke the sense of dreadfulness. By using this irony, it tries to influence the readers to judge that war is not kind at all. Walt Whitman’s Dirge for Two Veterans also points out death as the consequence of the war. But in this poem, misery is described as something that should be endured though it is haunting and frightening.